Vaccination against SARS-COV‑2 in oncology - A. A. Polyakov; V. V. Lunin; F. M. Abbaysbeyli; O. L. Timofeeva; V. B. Larionova; P. A. Zeynalova; A. A. Fedenko (Онкогематология, 2021)
The objective of the study a detailed, systematic review of the world literature data, which includes all aspects of recommendations for vaccination against SARS-COV‑2 in cancer patients.Materials and methods. Information search was carried out in PubMed, MedLine, Scopus, Web of Science, RSCI.The work included data from literature and information sources that were published before February 2021.Results. The data of retrospective and prospective clinical studies are analyzed. This paper reflects considerations and recommendations for the vaccination of cancer patients by Russian and foreign specialists in the context of COVID‑19 pandemic. The review presents current recommendations for vaccination against SARS-COV‑2 in patients with solid tumors, hematological malignancies, recipients of hematopoietic stem cells and cell therapy.Conclusion. To date, groups at increased risk of infection with the new coronavirus have been identified. These groups include patients with cancer. The presence of tumor does not allow a delay in start of therapy, and requires careful monitoring and observation. In this regard, despite the pandemic, the treatment of cancer patients must be continued regardless of the circumstances. Cancer patients should not be deprived of the opportunity to be vaccinated against SARS-COV‑2. Every patient should be decided individually. At the moment, there are no officially approved recommendations for vaccination against SARS-COV‑2 for cancer patients. Before the creation and approval of final recommendations for cancer patients, it is necessary to focus on compliance with sanitary and anti-epidemic measures and the prevention of COVID‑19 infection. The global cancer community continues to actively develop recommendations for the optimal vaccination against SARS-COV‑2 in cancer patients.The most relevant ones are outlined in this article.